A Study of the Interaction Between Inviscid Flow and a Cantilevered Flexible Plate - Evetts, Reilly Owen George (Curtin University, 2017)
New models are presented which explore the fluid-structure interaction between a cantilevered flexible plate and ideal flow, giving rise to an utter instability. Firstly, it is shown that the fluid-to-plate density ratio must be considered when the wake is modelled. Secondly, at large amplitudes flow separation can give rise to sub-critical instability, elucidating on cause of the hysteresis loops observed in the literature.